Effects of workplace incivility, negative affectivity and hurt feelings on coworker helping - Ida Rosnita Ismail; June M. L. Poon; Rasidah Arshad (Penerbit Universiti Kebangsaan Malaysia, 2018)
Helping behavior among coworkers is important in ensuring organizational functioning. Some researchers propose that the presence of negative work behavior, such as workplace incivility, may reduce helping behavior among coworkers. Research testing the effects of workplace incivility on coworker helping is, however, limited. Therefore, this study sought to address this research gap. Underpinned by affective events theory, the theory of reasoned action, and the norm of reciprocity, this study examined the relationship between workplace incivility and coworker helping using a mediation-moderation framework with hurt feelings as a mediating variable and negative affectivity as a moderating variable. The study sample comprised 463 employees of a public sector organization in Malaysia. The study hypotheses were tested using PLS structural equation modeling. The results of the study showed that (a) workplace incivility was negatively related to coworker helping, and this relationship was mediated partially by hurt feelings, (b) workplace incivility and negative affectivity were both positively related to hurt feelings, (c) hurt feelings was negatively related to coworker helping, and (d) negative affectivity did not moderate the relationship between workplace incivility and hurt feelings. Theoretically, this study contributes to the literature by providing some support for (a) the presence of tit-for-tat exchanges in cases of workplace incivility, (b) the importance of examining discrete emotions in organizational research, and (c) the importance of affective events theory for explaining the link between a work event and a behavioral intention. This study also informs employers and human resource practitioners that workplace incivility is a real and costly problem; thus, appropriate managerial interventions are needed to address this issue.